The impact of bisphenols on reproductive system and on offspring in pigs - A review 2011-2020 - Bahelka, Ivan; Stupka, Roman; Čítek, Jaroslav; Šprysl, Michal (Chemosphere, 2021)
This study summarizes the knowledge about effects of bisphenol A (BPA) and its analogues on reproduction of pigs and some parameters of their offspring during period 2011-2020. Bisphenols are known as one of the most harmful environmental toxicants with endocrine-disrupting properties. One study in the reference period related to male reproductive system. Treatment with an antagonist of G-protein coupled estrogen receptor (GPER) - G15, and bisphenol A and its analogues, tetrabromobisphenol A (TBBPA) and tetrachromobisphenol A (TCBPA) diversely disrupted protein molecules controlling the biogenesis and function of microRNA in Leydig cells. Nine studies examined the effect of BPA, bisphenol S (BPS) or fluorene-9-bisphenol (BHPF) on female reproductive system. From the possible protective effect's point of view seems to be perspective the administration of melatonin in BPA-exposed oocytes. Finally, two studies were found to evaluate the maternal exposure to BPA on offspring's meat quality, muscle metabolism and oxidative stress. Administration of methyl donor improved antioxidant enzymes activity and reduced oxidative stress in piglets.
Keywords: fenoly; Endocrine Disruptors; Animals; Phenols; Leydigovy buňky; endokrinní disruptory; Female; zvířata; mužské pohlaví; Benzhydryl Compounds; Leydig Cells; Male; prasata; Swine; ženské pohlaví; benzhydrylové sloučeniny